Application of neurodevelopmental screening to a sample of South American infants: the Bayley Infant Neurodevelopmental Screener (BINS) - McCarthy, Ann Marie (2012)
Objective: To evaluate the utility of the Bayley Infant Neurodevelopmental Screener (BINS), standardized in the US, for South American infants, 3-24 months of age. Methods: Thirty-five physicians administered the BINS to 2471 South American infants recruited during routine well-child visits, 578 (23%) from Brazil and 1893 (77%) from six other South American countries. The BINS was translated into Spanish and Portuguese and participating physicians were trained to administer the BINS. Physician inter-rater agreement with training tapes was 84.4%; test-retest reliability for age item sets ranged from 0.80 to 0.93 (Pearson's r). Infants were classified into being at low, moderate, or high risk for developmental delay or neurological impairment based on their total BINS score. The sample was stratified by infant's age, sex and language (Spanish and Portuguese). The BINS scores were compared to the scores of the US infant sample used to standardize the BINS. Results: Female infants performed higher than male at 16-20 months and 21-24 months; male infant scores were more variable at 5-6 months. Scores on only two items were significantly different between Spanish and Portuguese speaking participants. South American scores were typically significantly higher than the US sample, and a lower proportion of infants were classified as being at high risk in the South American sample than in the US standardization sample. Conclusion: Overall, the results of this study indicate that the BINS is feasible and appropriate for neurodevelopmental screening in South America. Further studies are needed to confirm the BINS utility in South America, including its use with a clinical sample.